TRANSFORMATION OF THE IDEA OF A UNIVERSITY IN MODERN SOCIETY - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
New calls of modern world bring in substantial corrective amendments in the idea of university education, keeping humanistic potential of fundamental knowledge and its connection with dominant type of culture.